Progranulin mutations and amyotrophic lateral sclerosis or amyotrophic lateral sclerosis–frontotemporal dementia phenotypes. Issue 7 (19th March 2007) - Schymick, J C; Yang, Y; Andersen, P M; Vonsattel, J P; Greenway, M; Momeni, P; Elder, J; Chiò, A; Restagno, G; Robberecht, W; Dahlberg, C; Mukherjee, O; et al.
Abstract : Objective: Mutations in the progranulin ( PGRN ) gene were recently described as the cause of ubiquitin positive frontotemporal dementia (FTD). Clinical and pathological overlap between amyotrophic lateral sclerosis (ALS) and FTD prompted us to screen PGRN in patients with ALS and ALS–FTD. Methods: The PGRN gene was sequenced in 272 cases of sporadic ALS, 40 cases of familial ALS and in 49 patients with ALS–FTD. Results: Missense changes were identified in an ALS–FTD patient (p.S120Y) and in a single case of limb onset sporadic ALS (p.T182M), although the pathogenicity of these variants remains unclear. Conclusion: PGRN mutations are not a common cause of ALS phenotypes.